1983
DOI: 10.1113/jphysiol.1983.sp014707
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive doublets in human flexor carpi radialis muscle.

Abstract: SUMMARY1. Single-motor-unit activity was recorded from flexor carpi radialis of two human subjects.2. A large number of units showed repetitive doublets at the onset of slow recruitment. A unit starting with doublets would transfer to a normal firing pattern as the force increased.3. At different speeds of ramp contractions, the number of doublets discharging at the onset of contraction decreased as the speed of contraction increased.4. Both low-and high-threshold units discharged repetitive doublets. Motor un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
114
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 22 publications
15
114
3
Order By: Relevance
“…In contrast, 45 % (9 of 20) of the F cells showed doublet firing. Doublet discharge in motoneurons has been reported in a variety of experimental preparations including (1) healthy humans during weak voluntary contractions (Bawa & Calancie, 1983), (2) reflexive motor unit recruitment in decerebrate cats (Cordo & Rymer, 1982), (3) controlled locomotion in decerebrate cats (Zajac & Young, 1980), (4) intracellular current injection in cat motoneurons (Calvin, 1975), and (5) various pathological conditions in humans (Koenig & Stoehr, 1986). Interestingly, doublets were not observed in the intracellular study of Kernell & Monster (D. Kernell, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 45 % (9 of 20) of the F cells showed doublet firing. Doublet discharge in motoneurons has been reported in a variety of experimental preparations including (1) healthy humans during weak voluntary contractions (Bawa & Calancie, 1983), (2) reflexive motor unit recruitment in decerebrate cats (Cordo & Rymer, 1982), (3) controlled locomotion in decerebrate cats (Zajac & Young, 1980), (4) intracellular current injection in cat motoneurons (Calvin, 1975), and (5) various pathological conditions in humans (Koenig & Stoehr, 1986). Interestingly, doublets were not observed in the intracellular study of Kernell & Monster (D. Kernell, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Collision experiments suggest that facilitation causes some motor units to discharge twice or more with an interval of about 4 ms. Bawa & Calancie (1983) have shown that forearm flexor motor units can discharge as doublets with interspike intervals within this range. Multiple firing of motor units has also been shown to arise from single electrical brain shocks in humans (Day et al 1986b).…”
Section: Discu-ssionmentioning
confidence: 99%
“…However, motor units sometimes discharge doublets with short intervals followed by longer-than-average intervals, and successive intervals may be correlated negatively (Andreassen and Rosenfalck 1980). Under certain conditions, this alternation of short and long intervals may be accentuated (Bawa and Calancie 1983;Elble and Randall 1976). Andreassen and Rosenfalck (1980) adduced three possible mechanisms for such patterns: summation of motoneuronal afterhyperpolarization, recurrent inhibition and proprioceptive feedback.…”
Section: Physiological Significancementioning
confidence: 99%